Theorical study on mechanical properties of AZ31B Magnesium alloy Sheets under multiaxial loading (Fracture and Structural Integrity, 2016)
Numerical simulation by plastic deformation of the shaping processes currently has a large industrial interest. It allows you to shorten the time of design and construction related products and tools to analyze and to optimize processes. An essential part of simulation tools is the constitutive law used to describe the material used. The activity of characterization and modeling of material behavior of the plastic deformation shaping remains a very important research field of activity; the objective of proposing laws of behavior used in computer codes, essentially based on finite element is sufficiently to represent the real behavior of materials. Considering the nature of the materials used and the stresses they experience the behavior laws account for several requirements which make them increasingly complicated. Among these requirements, we cite in particular plastic anisotropy, the great transformations, the complexity and diversity of loads, etc. The complexity of these laws makes them more difficult to implement and in particular to identify: the classic tests are no longer sufficient for identification. The objective of this work is based on two essential points: Suggest a construction strategy, particularly of identifying laws elastoplastic behavior anisotropic operational for the numerical simulation of plastic deformation shaping processes with particular attention to sheet metal magnesium. Magnesium sheet metal manufacturing process involves rolling operation. In a cost-cutting goal, this operation now takes place cold, implying a very marked anisotropy of the material at the output of the mill.
Keywords: Mechanical behavior; Tensile test; Loading direction; Lankford coefficient; Identification